2015
DOI: 10.1210/jc.2014-4033
|View full text |Cite
|
Sign up to set email alerts
|

Increased Abdominal Adiposity in Adolescents and Young Adults With Classical Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency

Abstract: CAH adolescents and young adults have increased abdominal adiposity, with a higher proportion of proinflammatory VAT than SAT. An improved understanding of the mechanism of obesity in CAH may lead to targeted prevention and therapeutics in this high-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
6
43
1
Order By: Relevance
“…Chronically, intermittently elevated adrenal androgen levels due to shortcomings of current therapy in both males and females may be one of the reasons that there was no difference in obesity status between sexes within subtypes. A recent study reported higher visceral and subcutaneous fat measured by computed tomography imaging in 28 adolescents and adults with CAH compared to healthy controls; the study found no difference in visceral or subcutaneous fat between sexes and found no correlation with glucocorticoid dosing …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Chronically, intermittently elevated adrenal androgen levels due to shortcomings of current therapy in both males and females may be one of the reasons that there was no difference in obesity status between sexes within subtypes. A recent study reported higher visceral and subcutaneous fat measured by computed tomography imaging in 28 adolescents and adults with CAH compared to healthy controls; the study found no difference in visceral or subcutaneous fat between sexes and found no correlation with glucocorticoid dosing …”
Section: Discussionmentioning
confidence: 90%
“…Body composition of children with CAH is an emerging area of focus, and recent data indicate that body mass index (BMI) and/or fat mass is elevated in children and adults with CAH . In normal growth, BMI increases rapidly in infancy and peaks at around the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was the first to use DXA to calculate VAT in children with CAH and found no difference in VAT between cases and controls. Only one previous study, by Kim et al, quantitated VAT in children with CAH using a computed tomography scan and found increased VAT in 28 children with CAH. Several factors other than the measurement method may account for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…et al,32 quantitated VAT in children with CAH using a computed tomography scan and found increased VAT in 28 children with CAH. Several factors other than the measurement method may account for this difference.…”
mentioning
confidence: 99%
“…Our findings in CAH, compared to a BMI-matched cohort, suggest that individuals with classical CAH due to 21-hydroxylase deficiency may not develop subclinical atherosclerosis in adolescence. Nevertheless, since it is known that CAH confers a higher relative risk for obesity and adiposity in childhood and adolescence [5,6,34], it remains concerning that obese CAH subjects exhibit higher CIMT than their non-obese counterparts.…”
Section: Discussionmentioning
confidence: 99%